Your voice at work : global report under the follow-up to the ILO Declaration on Fundamental Principles and Rights at work (ILO GenevaCH, 2000)
Underscores the crucial role of freedom of association and the effective right to collective bargaining in achieving decent work for all in today's globalizing world. Outlines the challenges and opportunities that accelerated structural and technological change has brought in its wake. Examines trends in relation to the respect shown for these principles and rights around the globe. Stresses how good governance of the labour market based on respect for these principles and rights can contribute to stable economic, social and political development.
Keywords: FREEDOM OF ASSOCIATION